Organic Carbon Determination in Acid Sulphate Soils - Jusop, Shamsuddin; I., Jamilah; J. A., Ogunwale (Universiti Putra Malaysia Press, 1994)
Pyrite is almost exclusively present in the reduced zone of acid sulphate soil Profiles. This pyrite is believed to interfere with determination of Cmg in the soils by the wet combustion method using Cr2o7 A study was conducted to determine an accurate and reliable method for estimation of Cmg in acid sulphate soils in Malaysia containing variable amounts of pyrite. Some of the established methods of carbon (C) determination were tested against Carbon Determinator (Leco IR-312) which was regarded as the standard method. It was found that the interference of pyrite in the determination of C in acid sulphate soils by wet combustion was minimal. The total oxidation procedure was found to be the most reliable and accurate method for determination of C in acid sulphate soils in the absence of Carbon Determinator. The Walkley-Black method underestimated, while the loss on ignition method overestimated the Cmg content in the soils.